2020
DOI: 10.3390/life11010004
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Fusion Rules to Describe Codon Assignment in the Standard Genetic Code

Abstract: We propose combinatorial fusion rules that describe the codon assignment in the standard genetic code simply and uniformly for all canonical amino acids. These rules become obvious if the origin of the standard genetic code is considered as a result of a fusion of four protocodes: Two dominant AU and GC protocodes and two recessive AU and GC protocodes. The biochemical meaning of the fusion rules consists of retaining the complementarity between cognate codons of the small hydrophobic amino acids and large cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 91 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…Any amino acid, even a noncanonical one, could take part in the beginning of coded peptide synthesis. The same point of view is substantiated by Nesterov-Mueller et al [89] in a recent original, yet too speculative hypothesis of "fusion of four independently coexisting protocodes." Even the authors admit that it is not clear how these protocodes could have arisen.…”
Section: Transition From Noncoded To Codedsupporting
confidence: 55%
“…Any amino acid, even a noncanonical one, could take part in the beginning of coded peptide synthesis. The same point of view is substantiated by Nesterov-Mueller et al [89] in a recent original, yet too speculative hypothesis of "fusion of four independently coexisting protocodes." Even the authors admit that it is not clear how these protocodes could have arisen.…”
Section: Transition From Noncoded To Codedsupporting
confidence: 55%
“…The combinatorial fusion of AU- and GC-protocodes proposed by Nesterov-Mueller and Popov absorbed these ideas of the competing entities and the separated AU and GC early phases [ 34 ]. It described with surprising simplicity the codon assignments in the SGC, including the codons for the non-canonical amino acids, the appearance of stop codons, as well some deviations from the SGC in mitochondria [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The fusion rules for the recessive protocodes are based on the same mutations, but in the 1st position or in positions 1 and 3. Having identified this fact from the fusion cascade, Nesterov-Mueller et al suggested that such combinations could be induced within the framework of the kissing hairpin geometry by means of complementary codons [ 32 ]. Attempts to explain the emergence of the genetic code from complementary tRNA hairpins were also undertaken by Rodin and Ohno [ 35 ].…”
Section: Combinatorial Fusion Cascade and Its Formalismmentioning
confidence: 99%
“…The recent discovery of the fusion rules integrated into the SGC led to a simple and mathematically exact description of the codon distribution over canonical amino acids [ 31 , 32 ]. According to these rules, the modern genetic code arose from the fusion of dominant and recessive protocodes, which initially competed for the same triplets.…”
Section: Introductionmentioning
confidence: 99%